Isolation, characterization and antibacterial activity of Lactic Acid Bacteria from commercial honey marketed in Malaysia - Mohamed Mustafa Aween
A total of 32 lactic acid bacteria (LAB) were isolated from 13 honey samples commercially marketed in Malaysia, and six strains identified as (Lactobacilus acidophilus) by API CHL50 were evaluated for their antibacterial activities against multiple antibiotic resistant (Staphylococcus epidermis), (Bacilus subtilis), (Salmonella typhimurium), (Escherichia coli), (Klebsiella pneumoniae), (Shigella sonnei), (Serretia marcescens) and (Enterobacter aerogenes). Using the overlay agar method the inhibition zone varies with target bacteria which were (S. aureus) 25 to 32 mm, (Staphycoloccus epidermis) 14 to 22 mm, (Bacillus subtilis) 12 to19 mm, (Salmonella typhimurium) 23 to 30 mm, (E. coli) 7 to 18 mm, (Klebsiella pneumoniae) 13.5 to 21.5 mm, (S. sonnei) 9 to 22 mm, (Serretia marcescens) 7.5 to 18 mm, and (E. aerogenes) 10 to 18 mm after 24 h incubation at 30 degree celcius. The effects of temperature, protolithic enzymes and pH on the antibacterial activity of the supernatants were evaluated. The supernatant was stable at 90 degree celcius and 121 degree celcius for 1 hour. Treatment with proteinase K and RNase II maintained the antimicrobial activity of all the supernatants ecxept H006-A from Libyan honey and H010-G from New Zealand honey. All the supernatants showed antimicrobial activities against target bacteria at pH 3 and pH 5 but not pH 6 except against (Enterobacter aerogenes) within 48 h incubation at 30 degree celcius. (Staphylococcus aureus) was not inhibited by H006-A isolated from Libyan honey and H008-d isolated from Malaysian honey at pH 5, compared to supernatants from other (L. acidophilus) isolates. Result from PCR identified LAB isolates as uncultured bacteria. Eight primers were used for RAPD and primer P69 highly discriminated the six isolates. The results from RAPD suggested that the strains of (Lactobacillus acidophilus were different from each other depending on the source of honey.